2018
DOI: 10.5115/acb.2018.51.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous spermidine ameliorates tubular necrosis during cisplatin nephrotoxicity

Abstract: The hallmark of cisplatin-induced acute kidney injury is the necrotic cell death in the kidney proximal tubules. However, an effective approach to limit cisplatin nephrotoxicity remains unknown. Spermidine is a polyamine that protects against oxidative stress and necrosis in aged yeasts, and the present study found that exogenous spermidine markedly attenuated tubular necrosis and kidney dysfunction, but not apoptosis, during cisplatin nephrotoxicity. In addition, exogenous spermidine potently inhibited oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In mice, genetically ablation of SSAT and SMOX inhibit tubular injuries and restore kidney function after AKI, suggesting a critical role of endogenous polyamine metabolism in the pathogenesis of kidney injuries (Zahedi et al 2009 , 2010 , 2014 , 2017 ). Importantly, exogenous addition of spermidine displays a protective role against kidney injuries induced by a variety of stimuli, including cisplatin, and ischemia–reperfusion injury (Kim 2017a , b ; Yoon and Kim 2018 ). In addition, a recent study revealed that polyamine metabolism is altered in focal segmental glomerulosclerosis and highlighted a crucial role of spermidine in maintaining filtration barrier, suggesting polyamine metabolism is also important in the pathogenesis of chronic kidney diseases (Liang et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, genetically ablation of SSAT and SMOX inhibit tubular injuries and restore kidney function after AKI, suggesting a critical role of endogenous polyamine metabolism in the pathogenesis of kidney injuries (Zahedi et al 2009 , 2010 , 2014 , 2017 ). Importantly, exogenous addition of spermidine displays a protective role against kidney injuries induced by a variety of stimuli, including cisplatin, and ischemia–reperfusion injury (Kim 2017a , b ; Yoon and Kim 2018 ). In addition, a recent study revealed that polyamine metabolism is altered in focal segmental glomerulosclerosis and highlighted a crucial role of spermidine in maintaining filtration barrier, suggesting polyamine metabolism is also important in the pathogenesis of chronic kidney diseases (Liang et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…ROS has an important role in a variety of kidney disease models. H 2 O 2 , a diffusible reactive oxygen metabolite formed by either enzyme-catalyzed or spontaneous dismutation of superoxide anion, has been implicated in the pathogenesis of tissue damage in acute kidney injury including ischemia reperfusion injury [495051] and cisplatin nephrotoxicity [161718]. H 2 O 2 inflicts oxidative stress at multiple cellular sites either directly or indirectly through generation of more reactive intermediates [12], acting as an indirect activator of p53, MAPK, and AKT [5253], and modulating mitochondrial function [54].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, H 2 O 2 has been used to understand the pathogenesis of various tissue damages and the induction of cell death [12]. Furthermore, exogenous and endogenous H 2 O 2 is considered to be an important mediator of kidney tubular injury in a variety of situations including kidney ischemia reperfusion injury [131415], cisplatin nephrotoxicity [161718], glomerulonephritis [19], and ureteral obstruction [202122]. Among kidney tubular segments, kidney proximal tubules are more susceptible to cell injury and death than kidney distal tubules during these situations [23].…”
Section: Introductionmentioning
confidence: 99%
“…Male C57BL/6 mice, aged 8 to 10 wk, were purchased from Orient Bio (Seongnam, Republic of Korea), maintained on a 12-h light/12-h dark cycle at 23°C with 55% humidity, and allowed free access to water and standard mouse chow. Mice received intraperitoneal injection with cisplatin (a single dose of 10, 20, or 30 mg/kg body wt; Sigma, St. Louis, MO) to induce nephrotoxicity or with 0.9% saline (control), as described previously (17,21,46). Briefly, cisplatin solution for mice was prepared at 1 mg/mL cisplatin in 0.9% saline.…”
Section: Animal Preparation and Cisplatin Nephrotoxicitymentioning
confidence: 99%